THE EFFECT OF QUALITY OF WORK LIFE AND ORGANIZATIONAL COMMITMENT ON PERFORMANCE WITH MODERATION OF ORGANIZATIONAL CULTURE: STUDY ON PUBLIC HEALTH CENTER PUSKESMAS IN GABUS DISTRICT - Astuti , Jannah Puji; Soliha , Euis (International Journal of Social and Management Studies, 2021)
This study aims to determine the effect of the quality of work life and organizational commitment on performance by moderation of organizational culture of the study on health workers at the puskesmas in Gabus District, Pati Regency. This research was conducted on 108 employees at the Puskesmas Gabus District, Pati Regency . The sample takes the entire population to be used as a research sample. Data analysis using SPSS software tools. The results of the study found that the quality of work life has a positive effect on employee performance at the Gabus Health Center. Organizational commitment has a positive effect on performance of employees of the Gabus Health Center. Organizational culture moderates the effect of quality of work life on employee performance at the Gabus Health Center. Organizational culture moderates the effect of organizational commitment on employee performance at the Gabus Health Center.